2012
DOI: 10.1155/2012/624792
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Endodontic Retreatment of Advanced Inflammatory External Root Resorption Using Mineral Trioxide Aggregate Obturation

Abstract: Inflammatory external root resorption is one of the major complications after traumatic dental injury. In this case report, we describe treatment of a maxillary central incisor affected by severe, perforating external root resorption. An 18-year-old patient presented with a previously traumatized, root-filled maxillary central incisor associated with pain and sinus tract. Radiographic examination revealed periradicular lesion involving pathologic resorption of the apical region of the root and lateral root sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Ritter et al (2004) showed that the continuation of root formation and revascularization occurs only if the root canal is bacteria-free (Saoud et al, 2016). Nonetheless, growing evidence supports the conclusion that RET can arrest EIR with dentine resorption on the lateral wall (Aggarwal & Singla, 2010;Priya et al, 2016;Santiago et al, 2015;Saoud et al, 2016;Utneja et al, 2012). Moreover, it has been shown that growth factors from the blood clot, and those embedded in dentine, are critical for the regenerative process by promoting biological healing (Galler et al, 2016;Yoshpe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ritter et al (2004) showed that the continuation of root formation and revascularization occurs only if the root canal is bacteria-free (Saoud et al, 2016). Nonetheless, growing evidence supports the conclusion that RET can arrest EIR with dentine resorption on the lateral wall (Aggarwal & Singla, 2010;Priya et al, 2016;Santiago et al, 2015;Saoud et al, 2016;Utneja et al, 2012). Moreover, it has been shown that growth factors from the blood clot, and those embedded in dentine, are critical for the regenerative process by promoting biological healing (Galler et al, 2016;Yoshpe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The first study describing the arrest of EIR with lateral root surface involvement by means of RET using TAP as intracanal medication and apical blood clot to repair apical periodontitis and pulp was published in 2012 (Miller et al, 2012 ). Subsequently, other case reports and case series have been published (Table 2 ), providing ample evidence that RET might be an efficient tool for treating and arresting EIR (Aggarwal & Singla, 2010 ; Chitsaz et al, 2021 ; Miller et al, 2012 ; Priya et al, 2016 ; Santiago et al, 2015 ; Saoud et al, 2016 ; Utneja et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Development of new bioactive material such as MTA makes possible other therapeutic approaches including the obturation of root canal space in complex cases of pathologic root resorption. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…Various irrigating solutions have been used to remove TAP, but information is limited on this issue (Utneja et al . , Bezgin et al . , Tawfik et al .…”
Section: Introductionmentioning
confidence: 99%